Integrating preventive and curative non‐chemical weed control strategies for concrete block pavements. (31st October 2013) - De, B; Fagot, M; Beeldens, A; Boonen, E; Bulcke, R; Reheul, D; Hatcher, Paul
Summary Reduction in herbicide use in non‐agricultural areas is being imposed by a growing number of governments, triggering the development of alternative strategies for weed prevention and control. This study aimed to determine the weed preventive abilities of different paving types, the required treatment frequency of non‐chemical weed control scenarios on these pavements and the associated weed species composition. A test parking area, constructed with four concrete paving types, was sown with a mixture of dominant weed species. Six scenarios with repeated use of a single weed control method (brushing with waste removal, hot air, selective application of hot water and three scenarios with flaming) and two scenarios with alternating use of brushes and hot air were applied to control the weeds during two growing seasons. Treatments were applied at well‐defined intervention moments, based upon weed development. Over 2 years, the paving types differed in weed coverage (up to a fourfold difference) and required varying treatment frequency (up to a 11‐fold difference) with lowest values for pavings with porous pavers. Within most paving types, up to 28% lower treatment frequencies were found for selective application of hot water, as compared with all other single method scenarios. Shifts in weed composition occurred in plots treated repeatedly with the same technique. Paving type determined the chances for the establishment of different weed species and alternating non‐chemical control methods with different modes of action offered the best opportunity to keep weeds under control.